Bioinformatic Analysis and Cellular Assays Identify Substance P Influencing Th17/Treg Differentiation via the MyD88 Pathway as a Potential Contributor to the Progression of Asthma and Allergic Rhinitis. (12th February 2022) - Ma, Yuemei; Liu, Chang; Xi, Guangpeng; Guan, Yuanyuan; Tang, Yao; Zhang, Jing; Xu, Yue
Abstract : Objective . This study is aimed at investigating the role of substance P (SP) in the development of asthma. Methods . The Gene Expression Omnibus (GEO) database was used to characterize SP expression in allergic rhinitis (AR) and asthma. Peripheral blood was collected from patients with asthma or AR. The expression of relevant cytokines and neuropeptides was measured. Enzyme-linked immunosorbent assay (ELISA) was also performed. The mast cell line LAD2 and the lung bronchial epithelial cell line BEAS-2B were treated with different concentrations of SP concentration. Then, the qRT-PCR method was used to determine the mRNA expression. Furthermore, p38 and p65 and their associated phosphorylated proteins (p-p38 and p-p65) were further validated by western blotting. Result . Clinical and GSE75011 data analysis suggested that MyD88 expression was upregulated in AR and asthma. Through the gene set variation analysis (GSVA), MyD88-related pathways were noticed and further investigated. ELISA results suggested that the SP expression was significantly increased in AR and asthma and IL-10 expression was decreased, whereas the expression of IL-6, IL-17A, IL-23, and TGF- β expressions increased. The mast cell line LAD2 was treated with different SP concentrations, and ELISA results showed that the expression of IL-6, IL-17A, IL-23, and TGF- β in the cell supernatant gradually increased with increasing SP concentrations, whereas that of IL-10 decreased. The lung bronchial epithelial cell line BEAS-2B was treated with different SP concentrations, and the expression of myeloid differentiation factor 88 (MyD88) and its related proteins was elevated. The expression of p38 and p-p38 proteins was elevated after SP treatment, and their expression levels elevated as SP concentrations increased. Finally, MyD88 expression at the single-cell level was also demonstrated. Conclusion . SP may affect the cytokine expression through the MyD88 pathway, thereby influencing Th17/Treg differentiation and eventually participating in the pathological process of asthma and AR. There are many pathological similarities between allergic rhinitis (AR) and bronchial asthma. In the present study, SP was found to possibly activate downstream inflammatory signaling pathways via MyD88, thereby affecting Th17/Treg differentiation and ultimately participating in the pathological process of asthma and AR.